The index system for project selection in ecological industrial park: A China study. (June 2017) - Wang, Qingsong; Lu, Shanshan; Yuan, Xueliang; Zuo, Jian; Zhang, Jian; Hong, Jinglan
Graphical abstract: Highlights: A comprehensive index system for projects selection in EIPs is established. Fuzzy Clustering Analysis is employed to simplify the comprehensive index system. Weights of system indicators are obtained with Fuzzy Analytic Hierarchy Process. Abstract: It is critical to extend and broaden the eco-industrial chain ( EIC ) by introducing new projects so that the stability of EIC network can be enhanced. At present, there is lack of effective control for project selection to eco-industrial park ( EIPs ) in China. This has led to low compatibility level of enterprises with the overall EIC network. By introducing the admission composite index, a framework is proposed in this study to assist the project selection in EIPs . It consists of three layers, i.e. target, criterion and variable. The preliminary index database is synthesized and simplified with Fuzzy Clustering Analysis ( FCA ). Fuzzy Analytic Hierarchy Process ( FAHP ) was employed to determine the weighting of each indicator. On the basis of the evaluation criteria, the evaluation method of the index system under two different conditions were established. This enriches the theory and methodology of ecological industry development in China. Meanwhile, the index system is effectively verified via an empirical case study. Results show that the index system is feasible, and quantitative results are consistent with the practice. These findings provide a good practical reference for the decision making of project selection in EIPs .